Mathematics E-Module as a Medium for Strengthening Students' Responsible Character - Herlina Yuriska; Tian Abdul Aziz; Lukman El Hakim (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
This study aims to analyze the role of mathematics e-modules as a medium for strengthening students’ responsibility character through a literature review approach using library research methods. The review includes relevant studies published within the last decade, covering trends in e-module development, the integration of character values in digital learning, and empirical findings on the effectiveness of e-modules in mathematics education. The results indicate that mathematics e-modules significantly enhance students’ conceptual understanding through interactive, flexible, and accessible learning materials. Additionally, e-modules contribute to fostering responsibility by encouraging independent learning, monitoring learning progress, and guiding learners through structured activities that require discipline. However, several limitations are noted, including infrastructure readiness, varying levels of digital literacy, and inconsistencies in e-module design quality. This study highlights the need for more comprehensive e-module development to optimize pedagogical functions while simultaneously strengthening character education in mathematics learning.